From e-learning to e-culture: a mentoring process for CPD development - Arici, Elaine (2019)
The study uses a mentoring approach to investigates the process of technological innovation from an end-user perspective to understand some of the factors that contribute to sustainable innovation practices within a higher education context. The aim is to bridge the gap between institutional technology innovation policy administration and the work-related factors that inhibit sustained technology innovation. Studies into the management process of e-learning adoption in Higher Education from a mentoring perspective is scarce, although there is a wide body of literature about e-learning technology uptake and user choice promoting improved learner outcomes. Many research studies report on the role of change agents within change processes but not how the underlying issues of managing the process of change is supported by mentoring. The research uses a case study approach within a voluntary CPD intervention, to establish the role that mentors as change agents play during the process of technological innovation. The study considered some of the working conditions that might support sustainable innovation development. Activity system analysis and the concept of contradiction (Engeström 2001) is the overarching analytical framework and toolset employed to understand the process of innovation within this context. The findings provided a valuable insight into the shifting roles of mentors as change agents from the participants’ perspective as they work towards their technological objectives. Concurrently, the research scrutinised the relational knowledge of mentors bases on an analysis of extrinsic and intrinsic motivational factors using the TPACK framework (Mishra and Koehler 2006). The study identified that relational knowledge of mentors identified as administrators, possessed the emergent content and declarative, procedural, conditional administrative knowledge (DPCAK). The results contribute to the understanding that a mentoring approach could support technology innovation in the wider context of 21st century HEIs, where technology use is now ubiquitous. However, it is vital that administrator mentors with DCPAK are acknowledged and utilised to support the process for sustained innovative practices. The mentoring approach and the acknowledgement of the relational knowledge of administrator mentors, will offer the means to support quick gains in technological development for the end user and, therefore, better efficiencies for the institutional context to which it is applied.